The introduction of REITs to the South African property market: Opportunities for fund managers - Naidoo, Hannalisha (My University, 2014)
On 1 May 2013, real estate investment trusts (REITs), a listed property product, had legislation about it introduced in the South African property market. Prior to the introduction of this REIT legislation, property unit trusts (PUTs) and property loan stocks (PLSs) were the two predominant types of listed property investment products in South Africa. However, both the PUT and PLS are subject to uneven regulation and taxation, and they lack flexibility. The REIT legislation was introduced to eliminate some of the problems of the PUTs and PLSs, by creating: a more unified tax treatment of listed property companies, more stringent regulatory requirements and uplifting the South African property market to a level that is internationally competitive. It is therefore considered valuable to empirically investigate whether or not the introduction of the REIT framework into the listed South African property market will be advantageous to investors, and whether or not it would lead to improvement in the efficiency, regulation and taxation of the listed property market. A questionnaire was used to collect primary data to analyze the research problem. The questionnaire used a Likert scale format that consisted of 20 questions. There were a total of 58 useable respondents, each of who fell into 1 of 5 occupational categories. The questions were divided into 4 unifying themes and the findings were analyzed according to these themes. From the analysis of the responses it was found that the REIT legislation is perceived as a welcomed and suitable introduction to the South African listed property market. We could also infer that REITs allow for a more favorable tax dispensation, improved regulation, increased international competitiveness and enhanced liquidity within the listed property market. Overall, there is a perception that investors, especially fund managers, would find it potentially advantageous to include South African REITs or a higher proportion of such REITs in their investment portfolios.
Keywords: Real estate investment trusts; Property market; South Africa; Investment; Legislation